State versus Market in developing countries in the twenty first century - Kalim Siddiqui (Institute of Economic Research (IER), 2015)
This paper analyses the issue of the state versus the market in developing countries. There was wide ranging debate in the 1950s and 1960s about the role of the state in their economy when these countries attained independence, with developing their economies and eradicating poverty and backwardness being seen as their key priority. In the post-World War II period, the all-pervasive 'laissez-faire' model of development was rejected, because during the pre-war period such policies had failed to resolve the economic crisis. Therefore, Keynesian interventionist economic policies were adopted in most of these countries. The economic crisis in developing countries during the 1980s and 1990s provided an opportunity for international financial institutions to impose 'Structural Adjustment Programmes' in the name of aid, which has proved to be disastrous. More than two decades of pursuing neoliberal policies has reduced the progressive aspects of the state sector. The on-going crisis in terms of high unemployment, poverty and inequality provides an opportunity to critically reflect on past performance and on the desirability of reviving the role of the state sector in a way that will contribute to human development.
Keywords: 330; 'Market-centric' model; role of the state; economic policy and developing countries